Calculation of the Magnetic Fields of the Electric Power Line - Patsiuk V.; Berzan V.; Rybacova G. (Problems of the Regional Energetics, 2016)
The task of calculation of per unit length parameters of multi-conductor electrical overhead transmission lines has been treated in the paper. The calculation of distribution of electric and magnetic fields has been performed by means of the finite volume method for entire span of the line. The theoretical justification of the method for calculation the parameters of electromagnetic field taking into account the change of the vector of magnetic potential along the line has been given. The problems of electrostatic and magnetostatic for a single electric conductor and unlimited long conductor with current have been solved. For the inner and total inductivities of a single conductor under the current have been obtained relationships and drawn dependences. Dependence between the speeds of light and of electromagnetic wave’s propagation has been presented. Based on the characteristics of distribution of electric and magnetic fields of multi-conductor lines has been provided the method of calculation of the matrix of own and mutual capacitances and inductivities the calculated values of per unit length parameters of compact 110 kV electric line which is in concordance with one of basic physical constant – the speed of light.